The Virtue of Waking Up at Fajr According to Hadith - Nadya Azzahra; Hasan Mud’is (Gunung Djati Conference Series, 2021)
This study aims to discuss the virtues of getting up at dawn according to the hadith. This research method is a type of qualitative research with literature study through a hadith approach. The results and discussion of this study include some of the virtues of waking up at dawn which are virtues themselves are very good for the body. This study concludes that there are so many virtues of getting up at dawn that one of the virtues is that angels pray for people at dawn. This study recommends especially for Islamic religious instructors to be able to provide understanding to the Muslim audience about the virtues of getting up at dawn according to the hadith.